2016
DOI: 10.1016/j.psychsport.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, burnout and engagement in youth sport: The mediating role of basic psychological needs

Abstract: Recent research indicates perfectionistic concerns and perfectionistic strivings share divergent associations with athlete burnout and athlete engagement. Guided by selfdetermination theory, the present study examined whether these associations were explained by basic psychological needs. Youth athletes (n = 222, M age = 16.01, SD = 2.68) completed measures of multidimensional perfectionism, athlete burnout, athlete engagement, basic psychological need satisfaction and thwarting. Structural equation modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 61 publications
15
101
0
6
Order By: Relevance
“…Recent empirical evidence shows that basic psychological need satisfaction and thwarting may help explain the perfectionism-athlete burnout relationship. For example, a cross-sectional study (Jowett, Hill, Hall, & Curran, 2016), examining a sample of junior athletes, found that lower need satisfaction and higher need thwarting mediated the positive cross-sectional association between perfectionistic concerns and burnout, whereas higher need satisfaction and lower need thwarting mediated the negative cross-sectional association between perfectionistic strivings and burnout. Future longitudinal research should, therefore, explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical evidence shows that basic psychological need satisfaction and thwarting may help explain the perfectionism-athlete burnout relationship. For example, a cross-sectional study (Jowett, Hill, Hall, & Curran, 2016), examining a sample of junior athletes, found that lower need satisfaction and higher need thwarting mediated the positive cross-sectional association between perfectionistic concerns and burnout, whereas higher need satisfaction and lower need thwarting mediated the negative cross-sectional association between perfectionistic strivings and burnout. Future longitudinal research should, therefore, explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Evaluative concerns are likely to undermine the three basic psychological needs, because EC is related to an overcritical self-evaluation (ie, frustration of competence), being externally driven and rigid (ie, frustration of autonomy), and social inflexible (ie, frustration of relatedness). 6,23,28 EC are also associated with insufficient coping strategies (ie, threat appraisal and avoidance coping) 29 and being less resilient when faced with adversity. 26,27,30 Previous research has shown associations between socially derived dimensions of perfectionism, such as EC, and a range of maladaptive and unhealthy outcomes including basic need frustration, 6,11 anxiety, 31 and decreasing performance development.…”
Section: Basic Need Frustration and Perfectionismmentioning
confidence: 99%
“…6,23,28 EC are also associated with insufficient coping strategies (ie, threat appraisal and avoidance coping) 29 and being less resilient when faced with adversity. 26,27,30 Previous research has shown associations between socially derived dimensions of perfectionism, such as EC, and a range of maladaptive and unhealthy outcomes including basic need frustration, 6,11 anxiety, 31 and decreasing performance development. 32 This is a paradox, as growth-oriented functioning, despite strain, is essential to thrive and succeed as an elite performer.…”
Section: Basic Need Frustration and Perfectionismmentioning
confidence: 99%
See 2 more Smart Citations